Histological organization of the subfornical organ of the albino rat. A histochentisuy study. - Daryanto, Daryanto (Universitas Gadjah Mada, 1994)
The objectives of this study are to provide an account of the well-established common histological characteristic of the subfornical organ, an overview of the controversial issues regarding its structure, and to point out the histological organization which is still unclear.This histochemistry study involving the light microscopy, transmission electron microscopy and scanning electron microscopy. The albino rats which did not receive any treatment were stained with several types of staining techniques for light microscopy, i.e. hematozylin-eosin, toluidin-blue, methylene-blue, the Russells acid-phosphotungstic-hematozylin, Bodians protargol, Weils hematozylin & ferriamonium-sulphate, and the Gomoris chrome-alum-hematozylin phlozine methods. This study was carried out in the Department of Histology, Faculty of Medicine, Gadjah Mada University, Yogyakarta by using 85 albino rats of the LMR (Lembaga Makanan Rakyat, Jakarta) strain. For transmission electron microscopy 19 albino rats were used: 10 adult albino rats of the LMR strain were done in LAKFIP UGM, Yogyakarta; five adult albino rats of the Wistar strain were done in Faculty of Graduate Studies, Mahidol University, Bangkok, Thailand; and four adult albino rats of the Wistar strain were done in First ...Key Words: subcomical organ - albino rat - neuron - neuroglia - ultra structures of blood capillaries